Kepemimpinan Transformasional Kepala Sekolah dalam Peningkatan Mutu Lembaga Pendidikan di SMK Ma’arif NU 02 Kemiri - Angely Nafachatul Muna; Adi Wibowo; Rosyidah Rosyidah (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines transformational leadership's role in improving educational quality at SMK Ma'arif NU 02 Kemiri, focusing on pedagogical quality and teacher professionalism. Vocational schools must respond to dynamic workplace changes while maintaining educational quality and character development, making transformational leadership, emphasizing inspiration, motivation, intellectual stimulation, and individual consideration—a strategic approach. Using qualitative literature review methodology, this research analyzed previous empirical studies and theoretical frameworks through systematic review and thematic analysis of scholarly articles on transformational leadership in vocational education contexts. Findings reveal transformational leadership significantly impacts three areas: (1) pedagogical quality improvement through innovative teaching methods and technology integration; (2) teacher professionalism enhancement via increased creativity, critical thinking, and learning design autonomy; and (3) collaborative work culture strengthening through improved communication and collective decision-making. Pedagogical quality emerges as the most significantly impacted indicator, manifested through teachers' capacity to develop adaptive strategies, implement student-centered pedagogies, and align vocational competencies with industry demands. Despite challenges including resistance to change and limited resources, transformational leadership effectively fosters sustainable school development, particularly in faith-based institutions integrating religious values with professional competencies, ultimately influencing institutional capacity and graduate employability.